ATLANTIC DIRECTION OF THE EXTERNAL POLICY OF THE PEOPLE’S PARTY (2011-2018) - N. A. Anikeeva (Ибероамериканские тетради)
The article notes that the cooperation of Spain with the United States during the study period, remains one of the priority directions of foreign policy of Madrid. Spanish analysts believe that bilateral relations are developing in a positive way, despite the fact that Spain, contrary to the will of the United States, in the spring of 2004 decided to withdraw their troops from Iraq. A special place in bilateral contacts is given to cooperation in the military-political sphere and in Economics. It should be noted that after a period of noticeable recession in the Spanish-American relations emerging in the years of the Bush presidency, when the Obama administration there has been a trend towards full normalization of the bilateral cooperation between Madrid and Washington NATO is considered in the Madrid basic element in the scheme of Euro-Atlantic security. Spanish military contingents have participated in NATO operations. While Madrid seeks to remain a loyal partner of the Alliance. Spain joined the anti-missile defence system (NMD) in Europe. At the same time, the Spanish administration has sought to actively defend its own national interests, and to have one’s own vision of European security issues. However, Madrid insisted on special attention to the issues of cooperation of NATO with countries of the Mediterranean, on the assumption that the main threats for Europe and Spain do not come from the East and from the South (terrorism, illegal migration).